Analisis Adopsi E-Commerce berdasarkan Kerangka TOE (Technology, Organization, Environment) pada UMKM Kota Bogor Indonesia - Alfi Rahmawati; Nurlela Machmuddin; Leni Lidya (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The MSME sector is one of the economic pillars in Bogor City, yet e-commerce adoption remains suboptimal despite the pressure of digital transformation. This study analyzes the determinants of e-commerce adoption using the Technology, Organization, Environment (TOE) framework. Using a quantitative correlational approach and simple random sampling, data were collected from 211 MSME actors, predominantly from the culinary and service sectors. The results demonstrate that technological readiness, organizational capability, and environmental support significantly influence adoption, with the model explaining 61.2% of the variance. The scientific novelty of this research lies in identifying the environmental factors, specifically government support and competitive pressure, as the most dominant driver (β = 0.368), surpassing internal technical and organizational factors in the urban MSME landscape. These findings contribute to the TOE literature by showing that, in emerging urban economies, digital transformation is primarily a reactive adaptation to external ecosystems rather than an internal readiness. Strategically, the results underscore the need for a holistic ecosystem approach to accelerate digital literacy and innovation among MSMEs.